Zonasi Konservasi untuk Siapa? Pengaturan Perairan Laut Taman Nasional Bali Barat - Amir Mahmud; Arif Satria; Rilus A. Kinseng (Jurnal Ilmu Sosial dan Ilmu Politik, 2015)
The zoning is not as usual and natural issues but complicated processes that determines allowed andprohibited activities of resources user. From economic views, zonation could potentially take advantagesand disadvantages, and socially it create a conﬂ ict as consequence of limited accesses. This research asqualitative research aims to observe zones utilization and it impacts to marine resource users in Bali BaratNational Parks (BBNP). The results show that utilization of marine zoning in BBNP is to ecology-biology protection, tourist and ﬁ sheries with resources user namely Boarding of BBNP, tourist company and ﬁ shers. Zoning results in regulating user activities including limited activities.